Recent Advances on Edible Films Based on Fruits and Vegetables-A Review - Otoni, Caio G.; Avena-Bustillos, Roberto J.; Azeredo, Henriette M. C.; Lorevice, Marcos V.; Moura, Marcia R. [UNESP]; Mattoso, Luiz H. C.; McHugh, Tara H. (Wiley-Blackwell, 2017)
Food packaging materials are traditionally expected to contain foodstuffs and protect them from deteriorating agents. Although petroleum-derived polymers have been widely used for this purpose, the rising concern with their nonrenewable and/or nonbiodegradable nature paves the route for the development of greener alternatives, including polysaccharides and polypeptides. The use of these food-grade biomacromolecules, in addition to fruits and vegetables, provides edible packaging with suitable physical-mechanical properties as well as unique sensory and nutritional characteristics. This text reviews the chronological development pathway of films based on fruit and vegetable purees, pomaces, and extracts. Recent advances are extensively reviewed with an emphasis on the role that each film component plays in the resulting materials, whose production methods are examined from a technical standpoint and essential properties are compiled and contrasted to their conventional, synthetic counterparts. Finally, this comprehensive review discusses advantages and limitations of edible films based on fruits and vegetables.
Keywords: active packaging; biodegradable material; biopolymer; food packaging; multifunctional film